The immunobiology of Fc receptors - Cragg, Mark (Henry Stewart Talks, 2021)
Cellular expression and function of Fc gamma receptors (FcγRs), IgG binding to FcγRs is modulated by carbohydrates, The consequences of FcγR ligation in immune cells is cell type specific, Roles of FcγRs in sculpting in the humoral immune response, FcγRs is a key regulator in antibody immunotherapy